Shoulder Glenolabral Articular Disruption Lesion Repair Using Suture Bridge Technique and Concomitant Panlabral Repair - Silvampatti Ramasamy Sundararajan, M.S.(Ortho); Kenchi Charith Nagarjun, M.S., D.N.B.(Ortho), D.S.I.C.O.T.; Terence Dsouza, M.S., D.N.B.(Ortho), F.N.B.(Sports Medicine); Rajagopalakrishnan Ramakanth, D.Ortho., D.N.B., D.S.I.C.O.T.; Bhupendar Singh, M.B.B.S., D.N.B.(Radiodiagnosis); Shanmuganathan Rajasekaran, M.S., F.R.C.S.(Ed), M.Ch.(Liv), Ph.D. (Arthroscopy Techniques, 2025)
Glenoid articular cartilage lesions are a source of shoulder pain and can occur in the setting of glenohumeral instability and degenerative shoulder disease. Glenolabral articular disruption (GLAD) lesions have been reported to be associated with worse outcomes after arthroscopic repair of labral tears. There are relatively few published studies evaluating outcomes after surgical treatment of glenoid articular lesions; however, it is generally accepted that management should consist of restoring the glenoid articular surface, minimizing the exposed articular defect, and re-establishing capsulolabral integrity to achieve stability. In this article, we describe our technique to address a GLAD lesion with a concomitant panlabral tear by performing both GLAD lesion repair and panlabral repair.